Effects of storytelling on user experience and performance in VR: a case study of Steady the drums! - Žnideršič, Klara; Pregelj, Zala; Pesek, Matevž (Frontiers in Virtual Reality, 2025)
IntroductionStorytelling is widely recognized as an effective tool for increasing engagement and motivation in digital games and learning environments. However, its application and impact in virtual reality (VR) is still under‐researched due to the relative novelty of VR technology. In this study we explore the integration of storytelling elements into the game Steady the Drums! and examine their impact on user experience, performance and overall game appeal.MethodsA comparative analysis was conducted with two groups: one group played a standard version of the game and the other a version enriched with a narrative. As the game aims to improve rhythm perception and skills, its impact on performance improvement in Tapping‐PROMS tests was also assessed.ResultsStorytelling improved the perceived hedonic qualities of the game and increased user engagement and interest. However, participants playing the storytelling version showed slightly lower focus and performance on rhythmic tasks compared to the non‐storytelling group. Despite this, both groups demonstrated significant improvements in rhythmic skills.Discussion The findings suggest that while storytelling enhances enjoyment and engagement, it may slightly reduce task‐focused performance in rhythm-based activities. Nevertheless, the observed improvement in rhythmic skills across both groups emphasizes the educational value of the game.